Automobile Trips to School and Safety Perspectives of Unplanned Lokoja Metropolis in North Central Nigeria - Musilimu Adeyinka Adetunji (Alanya Hamdullah Emin Paşa Üniversitesi, 2020)
Many studies on transport research did not consider the consequences of high reliance on an automobile trip to schools which frequently resulted in road traffic crashes, traffic delay, and late arrival to school, injuries and sometimes death of victims especially students. As a result, this research examines the consequences of automobile trip to school among secondary school students in the Lokoja metropolis. It aims to investigate the safety of the use of automobile in an unplanned city like Lokoja, with the specific objectives of ascertaining the number of pupils who embark on different automobile trips; the safety measures, and the casualty cases. Three hundred students were selected for questionnaire administration across six selected secondary schools in the city. Data on students’ road traffic crashes were obtained from archives. Descriptive and inferential statistics were employed for analyses. Findings reveal that more than 70% of students rely on automobile to travel to schools. Car trips to schools were more among students of private secondary schools. Students in private secondary schools rely more on the use of a school bus. It was also discovered that students were involved more in traffic crashes along major roads. The study concludes on the use of school bus by students instead of relying on private cars.